Demographic factors related to maternal and child attachment - Giraldo Montoya, Dora Isabel; Castañeda Palacio, Hellen Lucia; Mazo Álvarez, Héctor Mauricio (Universidad y Salud, 2017)
Introduction: Postpartum is one of the decisive moments to strengthen the attachment between the mother and child relationship; however, there are demographic factors that can limit this interaction and become a disadvantage for the proper development of the child. Objective: Determine the demographic factors related to maternal child attachment in the postpartum during the year 2014. Materials and methods: An analytical transversal study was carried out with a sample of 117 mothers with their newborn. The instrument Mother-child relationship was used. The variables to determine attachment were: breastfeeding, interest, response, language and tact. They were evaluated on a numerical scale whose final score allowed to determine whether there was a healthy or at-risk attachment. A logistic regression model was implemented to explore the association between demographic variables and at-risk attachment. Results: The median age was 27 years with an interquartile range between 22 and 31. 54.7% lived in free union and 34.2% had fulfilled high school studies. Healthy attachment was presented in 80.3% of the mothers. Nevertheless, 60.7% had low initial motivation for breastfeeding which could lead to at-risk attachment. Statistical association between at-risk attachment, marital status and schooling was found, but the only variable that explained this association was the civil status: single (RP = 4.88 IC 95% P = 0.48). Conclusion: According to the multivariate model, at-risk attachment is associated with the civil status: single.